Synthesis and characterization of some novel coumarin based various 2-aryl-pyrido [3,2-c] coumarins - Pandya, Mahesh K.; Parekh, Tapan H.; Chhasatia, Mehulsinh R.; Vala, Nileshkumar D. (Journal of Drug Delivery and Therapeutics, 2020)
A survey of the literature reveals that the number of coumarin derivatives having heterocyclic moieties either as substituent groups or fused with parent coumarin nucleus possesses a variety of functions and are widely used in drugs and dyes. Because of this wide utility, the synthesis of coumarin has remained a subject of active interest. Looking at the importance of these heterocoumarins and with a view to exploring new methods of their synthesis, the present work was undertaken and this synthesis deals with various 2-aryl-pyrido [3,2-c] coumarins. The compounds have been synthesized by reacting Mannich bases of various 4-hydroxy coumarins with pyridinium salts of various aroyl methyl bromides in the presence of ammonium acetate and acetic acid. All the compounds synthesized have been characterized by analytical and spectral data. Keywords: Pyrido, Coumarins, Krohanke’s reaction.